A novel RNA modification prognostic signature for predicting the characteristics of the tumor microenvironment in gastric cancer - Jing, Qiangan; Yao, Hongfeng; Li, Huanjuan; Yuan, Chen; Hu, Jiayu; Zhang, Ping; Wu, Yunyi; Zhou, Yi; Ren, Xueying; Yang, Chen; Lei, Guojie; Du, Jing; et al. (Frontiers in Oncology, 2023)
Gastric cancer (GC) is one of the most common neoplastic malignancies, which permutes a fourth of cancer-related mortality globally. RNA modification plays a significant role in tumorigenesis, the underlying molecular mechanism of how different RNA modifications directly affect the tumor microenvironment (TME) in GC is unclear. Here, we profiled the genetic and transcriptional alterations of RNA modification genes (RMGs) in GC samples from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) cohorts. Through the unsupervised clustering algorithm, we identified three distinct RNA modification clusters and found that they participate in different biological pathways and starkly correlate with the clinicopathological characteristics, immune cell infiltration, and prognosis of GC patients. Subsequently, univariate Cox regression analysis unveiled 298 of 684 subtype-related differentially expressed genes (DEGs) are tightly interwoven to prognosis. In addition, we conducted the principal component analysis to develop the RM_Score system, which was used to quantify and predict the prognostic value of RNA modification in GC. Our analysis indicated that patients with high RM_Score were characterized by higher tumor mutational burden, mutation frequency, and microsatellite instability which were more susceptible to immunotherapy and had a favorable prognosis. Altogether, our study uncovered RNA modification signatures that may have a potential role in the TME and prediction of clinicopathological characteristics. Identification of these RNA modifications may provide a new understanding of immunotherapy strategies for gastric cancer.